DESIGN SYNTHESIS OF NOVEL ACRIDINE TAGGED PYRAZOLE DERIVATIVES AS AURORA KINASE INHIBITORS - PERKA, HARATHI; D, SATYAVATI; REDDY GADE, DEEPAK; BOYA, VIVEKANANDA; PRASAD VVS, RAJENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A series of novel synthesis of 5-Substituted-3-phenyl-4,5-dihydro-pyrazole-1-carbothioic acid [4-(9, 10-dihydro-acridin-9-yl)-phenyl]- amide (IV) were synthesized using standard procedures and evaluated for cytotoxic studies. Methods: 9-(4-Chloro-phenyl)-9 and 10-dihydro-acridine (I) were formed by cyclization of diphenylamine with substituted acids in the prescience of zinc chloride and synthesis of 5-substituted-3-phenyl-4, 5-dihydro-pyrazole-1-carbothioic acid amide (3) by the cyclization of different chalcones (II) and final compounds were synthesized by fusion of 5-substituted-3-phenyl-4, 5-dihydro-pyrazole-1-carbothioic acid amide (III) with 9-(4-Chloro-phenyl)-9, 10-dihydro-acridine (I) by microwave irradiation method. Characterization of synthesized compounds by infrared, 1H nuclear magnetic resonance (NMR), 13C NMR, and mass spectroscopic methods. Obtained compounds were evaluated for their cytotoxicity against human breast cancer cell lines (MCF/wt) by sulforhodamine-B assay. Docking studies with Aurora kinase protein were performed to elucidate the possible mechanistic insights of these novel acridine tagged pyrazole derivatives. Results: Moderate to good in vitro cytotoxic potentials of the newly synthesized molecules was reported against selected human breast cancer cell lines. Among the tested molecules, compound C6 showed good cytotoxic activity against MCF/wt (08.2±0.4 μM). The dock scores of the tested compounds were ranged between −8.926 and −5.139. Compound C6 which has been reported as the most effective cytotoxic agent among the series also reported the highest dock score of -8.926 and showed hydrogen bond interaction with GLU-211, LYS-162, and LYS-143. Ligand binding energy with protein suggested compound C6 has shown the highest binding energy of −86.32133 kcal/mol. Conclusion: The in vitro studies of the newly synthesized acridine tagged pyrazole derivatives reported considerable cytotoxic potentials against human breast cancer cell lines and structure-activity relationship studies to suggest that acridine tagged pyrazole derivatives with hydroxy group present on phenyl ring at fifth position of pyrazole ring could probably increase the cytotoxic potentials. With the reported bioactivities of these derivatives, further studies on the derivatization could elucidate the broader cytotoxic potentials.